Feeding Time : The Feeding Habits of Animals - Walker, Theo (NewYork Cambridge University, 2014)
Do animals eat the way we do? Explore how cows and rabbits, seahorses, koalas, sharks, and more eat in ways that can be very, very strange to us.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Animals; Elementary level